1988
DOI: 10.1007/bf00004199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sulfur concentrations within lake sediment profiles

Abstract: Sediment cores from lakes in four regions (Adirondacks, Northern New England, Northern Great Lakes States, and Northern Florida) were analyzed for total S concentration. In all regions S concentrations in pre-1900 (1820-1900) sediment were similar and pre-1900 net sediment accumulation rates of S were not significantly different. Sulfur enrichment was greatest in Adirondack lake sediment (Big Moose L., Upper Wallface P., Queer L., and Deep L.), which had total post-1900 S accumulation of 1.1 to 7.4 times pre-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…If the reduced sulfur becomes permanently buried in the lake sediments, the gain in alkalinity becomes permanent (Giblin et al 1990). Such in-lake alkalinity generation through the burial of sulfides may be enhanced by elevated sulfate concentrations, changes in hypolimnetic anoxia, or increased delivery of organic matter to the sediments (Mitchell et al 1988;Murray 1994).…”
Section: Discussionmentioning
confidence: 99%
“…If the reduced sulfur becomes permanently buried in the lake sediments, the gain in alkalinity becomes permanent (Giblin et al 1990). Such in-lake alkalinity generation through the burial of sulfides may be enhanced by elevated sulfate concentrations, changes in hypolimnetic anoxia, or increased delivery of organic matter to the sediments (Mitchell et al 1988;Murray 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported elevated sulfur in recent sediments from lakes in the eastern U.S. and Canada (Nriagu and Soon 1985;Mitchell et al 1988;Carignan and Tessier 1988). Nriagu and Soon (1985) concluded that marked elevations in S concentrations are unlikely to be observed in lakes with [S0,2-] >5 mg l&x1 (100 I.leq liter-I); Mitchell et al ( 1988) reported mixed results for four upper midwest lakes, with two showing no recent enrichment and two showing enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Nriagu and Soon (1985) concluded that marked elevations in S concentrations are unlikely to be observed in lakes with [S0,2-] >5 mg l&x1 (100 I.leq liter-I); Mitchell et al ( 1988) reported mixed results for four upper midwest lakes, with two showing no recent enrichment and two showing enrichment. Although the increase in TS in our cores is small (l&62%), all four exhibit an increase beginnmg in the early 19009, clearly suggesting a relationship to increased atmospheric SOd2-deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Norton et al 1988). However, in one of these two cases (Mirror Lake), samples from the top 5 cm (most recent -30 yr) had lower concentrations of total S than recorded in sediment horizons predating 1900 (cf.…”
mentioning
confidence: 90%
“…However, two of their generalizations appear inadequately supported by the data, and two other geochemical relationships, although mentioned, seemingly deserve greater emphasis. In addressing these matters I also re-evaluate the paleolimnological data published by Norton et al ( 19 8 8) and Mitchell et al (1988).…”
mentioning
confidence: 99%